Foreign aid, foreign direct investment and economic growth in ECOWAS countries: Are there diminishing returns in the aid- growth nexus? - Hassan O. Ozekhome (West African Journal of Monetary and Economic Integration, 2017)
This paper investigates the impact of foreign aid and foreign direct investment (FDI) on economic growth in the Economic Community of West African States (ECOWAS) region, and whether diminishing returns occur in the aid-growth nexus, for the period 2000-2015, employing the Generalized Method of Moments (GMM) Estimator. The empirical results reveal that trade openness; foreign direct investment, real gross domestic capital formation, human capital and lagged real GDP (a measure of previous economic growth/market size) are the principal drivers of economic growth in ECOWAS countries. Foreign aid and its squared term (a measure of diminishing returns on account of absorptive capacity constraints) are both found to have negative impact on growth. Inflation (a measure of macroeconomic environment) is also found to have a dampening impact on economic growth in ECOWAS countries. We recommend amongst others; open trade and investment-enhancing policies (domestic and foreign), sound and stable macroeconomic policies, institutional structures, as well as policy coordination and harmonization with respect to trade and investment among member countries, to fast-track rapid economic growth, particularly in the quest for increased economic integration in the sub-region.
Keywords: F21; F35; F43; C13; 330; Foreign Aid; Foreign Direct Investment; Economic Growth; ECOWAS; Generalized Method of Moments (GMM)